Permasalahan Stunting Pada Anak Dan Penanggulangannya di Semambung, Kabupaten Sidoarjo - Andrea Caesarinda Daffa Ardhana; Ghulam Maulana Ilman (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
The problem of stunting is one of the vitamin problems that we face in general, especially in poor and developing countries. Stunting is a problem because it is associated with an increased risk of illness and death, and less than optimal brain development which results in motor delays and psychological retardation. Stunting is a form of slow development (failure to develop) due to the accumulation of vitamin deficiencies that occur from pregnancy until the age of 24 months. This situation continues to be exacerbated by the absence of sufficient catch-up growth. In Sidoarjo, the provisional figure for 2023 is that the number will increase to 16.3 percent. Meanwhile, in 2022 it will be 14.3 percent. The Sidoarjo Regency Government has once again demonstrated its commitment to overcoming the problem of stunting and improving children's welfare through the Bangga Kencana Consolidation and Convergence for the Acceleration of Stunting Reduction programs. This program aims to pay special attention to the growth and development of children and ensure that they grow and develop healthily. Through close collaboration between agencies, this program integrates various activities to achieve common goals, namely reducing stunting rates and improving children's quality of life.